THE EXPLOITATION OF AUDIENCE AS DIGITAL LABOUR IN INDONESIAN YOUTUBE PLATFORM (Profetik: Jurnal Komunikasi, 2021)
Abstract. In today's digital era, the internet is present in new media and has eliminated the boundaries between production and consumption space. Audiences are no longer just consumers but also actively participate in producing digital content that is uploaded and shared with other audiences. YouTube as one of the most consumed platforms by the audience has driven cultural change in the digital society. YouTube audiences are no longer simply enjoying content produced by the media as in the era of Television but they are watching content produced by other YouTube audiences. The YouTube audience is no longer the role of consumers but also as digital labours who are exploited above economic interests. This study aims to determine the role of the audience as digital labours in the YouTube industry in Indonesia. The research method used is digital discourse which will help researchers to uncover the motivations behind a text. The research results show that the YouTube audience is exploited in the accumulation of capital owners because their activities in producing culture and their attention to cultural content that generates data to attract advertisers' attention have resulted in profits for capital.